Village apparatus communication strategy in realizing harmony in Kemanukan Village, Purworejo - Ekastuti, Rachella Agnes (Institute of Computer Science (IOCS), 2024)
Harmony is a comfortable condition that every society desires. However, in reality, in Indonesia there are still many things that can shake this harmonious atmosphere, especially if you are in an area full of differences. Because of this, this research investigates the Communication Strategy employed by Village Officials in fostering harmony within the diverse community of Kemanukan Village, Bagelen District, Purworejo Regency, Indonesia. Utilizing a qualitative descriptive research method, the study delves into the non-verbal observations of the officials' attitudes, behaviors, and actions in maintaining societal harmony. Kemanukan Village, characterized by religious and belief diversity, necessitates vigilant administration to prevent potential conflicts. Village Officials play a crucial role in this context, utilizing communication strategies rooted in traditional and cultural values, as well as the principles of Pancasila. The results of this research show that communication is born when carrying out activities in society with existing traditions and cultural backgrounds The results that effective communication arises from engaging in social activities that promote unity among Kemanukan Village residents. Through these strategies, Village Officials contribute significantly to the creation and preservation of harmony, essential for the coexistence of the diverse community.